Defining the Cognitive Levels in Bloom’s Taxonomy through the Quranic Levels of Understanding - Initial Progress of Developing an Islamic Concept Education - Abidin, Syed Zainal; Bahrin, Syed Kamarul; Razak, Nur Firdaus Abdul (International Journal of Asian Social Science, 2013)
The cognitive domain of a Bloom’s taxonomy and the Quranic levels of understanding are elements in education that focus on the ability to think. However, there is currently no education system or method that is based on the Quranic levels of understanding due to the absence of proper definition. Therefore, this paper will provide general correlations between the cognitive levels and the Quranic levels of understanding so that the cognitive domain can be defined in term of Quranic levels of understanding. The authors anticipate that this initial progress can provide a catalyst for developing an Islamic Concept Education system.